A case of early neonate bovine tuberculosis in Ethiopia - Getnet Abie Mekonnen (Clinical Case Reports, 2021)
Abstract This report illustrates that calves may be infected with bovine tuberculosis at early age under natural conditions and progression can be rapid. Thus, testing of calves needs to be considered in any control program to reduce the risk of transmission.